Survey of Sports Facilities and Infrastructure at SMA Muara Telang - Suryadi, Imam; Wardiah, Dessy; Junaidi, Ilham Arvan (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aimed to evaluate the potential for standardizing physical education facilities and infrastructure in high schools within Muara Telang District, Banyuasin Regency. Using a quantitative descriptive method, the research was carried out in both public and private high schools throughout the district. The focus was on assessing facilities and infrastructure for large ball games, minor ball sports, and athletics. The objective was to determine the feasibility of standardizing these physical education resources. The results indicated that at SMA Negeri 1 Muara Telang, 50% of the sports facilities and infrastructure met the standard criteria, while the other 50% were classified as “lacking”. At Bina Muda High School, 40% of the facilities met the standard.